The important of environmental impact assessment (EIA) report in development project / Syifa Md Saad - Md Saad, Syifa (2010)
Environmental Impact Assessment (EIA) is a tool to evaluate the environmental effects of development project. It is essentially a planning mechanism for preventing environmental problems due to an action. It ensures that the potential problems are foreseen and addressed at an early stage in the project planning and design. Since it was first formally develop in the United States and become effective since January, 1, 1970, EIA has been widely discussed. Recently, our country had faced landslides disaster which had taken many innocent lives. The disaster mainly occurs in hillside area and it is because of the overdevelopment. The irresponsible developer who tends to ignore EIA report in conducting their project had contribute to the occurring significant impacts which eventually lead to environmental damages. The main aim of this project is to identify the importance of EIA in development projects. Besides, this study is also conducted to clearly explain the detail process and procedure of EIA and the problems of EIA report and application. At the end of this study, some opinions regarding effective steps for EIA continuous improvement in the future will also be discussed. Sources of the data and information are gathered by the author from literature review of previous researchers, academic writings, published articles, and supported by the opinions of practitioners through structured interviews.